Nursing Partnership Activities, Components, and Outcomes: Health Volunteers Overseas in Uganda 2001–2016 - Mbalinda, Scovia Nalugo; Nabirye, Rose Chalo; Ombeva, Elizabeth Ayebare; Brown, S. Danielle; Leffers, Jeanne M. (Frontiers in Public Health, 2017)
Abstract Word Count 117 Nurses increasingly form global health partnerships through academic and voluntary organizations that are designed to improve health outcomes. Many such partnerships are funded for specific time periods and have short or long term goals to achieve during the partnership. Other partnerships are sustained for longer periods of time through the efforts of partners committed to their joint work. The case example of the Health Volunteers Overseas (HVO) Nursing Education partnership in Kampala Uganda demonstrates key components of partnerships that promote sustainability of programs. This case example is analyzed using literature that reports partnership models to identify those factors that have led to sustainability. Additionally, both objective and subjective program outcomes are reported. Recommendations for further evaluation are included.